Impact if Lagging Region Status on Education in Indonesia - Negara, Gadis Mahkota (Syntax Corporation, 2024)
Place-based policies are commonly used in developing countries to stimulate economic development in underdeveloped regions. One such policy implemented by the Indonesian government, spanning from the presidency of SBY to Jokowi, involves designating certain districts as “lagging regions.” This study examines the impact of this designation on education during these two administrations, utilizing panel data from 2003 to 2018 across 514 districts in Indonesia. The analysis is divided into three periods, corresponding to different phases of the policy’s implementation. The education indicator used is the net enrollment ratio, with the special allocation fund (DAK) serving as the mediating variable. The findings are consistent across various empirical approaches, including propensity score matching, first difference, and panel data estimation. Despite these efforts, the designated lagging regions still have a lower net enrolment ratio than the non-lagging regions. The overall results suggest that there has been no convergence in the educational outcomes between the two groups of regions. This highlights the need for adequate resource mobilization to ensure the effectiveness of such place-based policies.